Rice cropping events data for Saldaña (lowland irrigated rice) and Villavicencio (rainfed rice), Colombia - Federación Nacional de Arroceros, Colombia (2015)
These two datasets hold basic information on rice cropping events corresponding to fields of two regions of Colombia: Saldaña (Tolima) and Villavicencio (Meta). This include municipality, variety, cropping system (irrigated/rainfed), sowing and harvesting date, and yield.